PERANCANGAN SISTEM INFORMASI PEMBANGUNAN JALAN PERDESAAN DI KABUPATEN SERANG (Studi Kasus Pada Desa Sukadalem Kecamatan Waringinkurung) - Widyawati Widyawati; Dedeh Ratnasari; Indra Gunawan (LPPM Unbaja, 2021)
The PUPR Service of Serang Regency is located on Jalan Sama’un Bakri, Lopang, Serang2City, where there are many areas of duty, one part of which is the development section of the development section, which has tasks in road construction. In recording or data collection, road construction still uses Microsoft Excel, so it is not effective because of data loss and data duplication. So we need a new system that can support these activities. With the website-based information system using the PHP programming language, the database used is MySQL and the Waterfall method makes this information system usable anytime and anywhere. The purpose of this study is to design a rural road development information system that can provide information to the government regarding road construction and can monitor the progress of road construction in progress. The community can also see this information without having to come to the PUPR Office of Serang Regency to ask about information on the construction of their village roads that will be built and can report complaints related to road conditions, especially in the Serang district area in the community complaint feature so that it can be immediately followed up by government.